Great names of Russian medicine — S. S. Zimnitsky and N. S. Korotkoff. Destinies and creativity (on the 150th anniversary of the scientists’ birthday and on the 120th anniversary of N. S. Korotkoff’s creation of auscultatory method of blood pressure measurement) - A. A. Terekhova; V. N. Oslopov (Кардиоваскулярная терапия и профилактика, 2025)
S. S. Zimnitsky and N. S. Korotkoff are great Russian scientists and doctors who have made an invaluable contribution to medicine. The beginning of their life path was approximately the same, but after receiving their medical degrees, their fates began to differ dramatically. The article presents a comparative analysis of the biographies of the two scientists. Their life path, which led to great discoveries in medicine, is shown.